EVALUASI KESUBURAN TANAH DI KEBUN KOPI DESA GIRSANG SIPANGAN BOLON, SIMALUNGUN - Ramadhan, Akbar Syam; Adrian, Rama; Chaniago, Almunazza Kani; Siregar, Faiq Raihan Zaky; Saputra, Ridho; Mahany, Chalisa (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
This research aims to assess the soil fertility conditions in a coffee cultivation area in Girsang Sipangan Bolon Village, Simalungun Regency. This evaluation is conducted by examining both physical and chemical soil characteristic at two sampling depths: 0-20 cm and 20-40 cm. Key indicator analyzed include bulk density, water retention capacity, pH levels, and organic matter content. The findings indicate that the soil’ bulk density (ranging from 1.06 to 1.07 g/cm3) is within optimal parameters, moisture retention at field capacity is notably high (44.92% to 47.06%), and the organic matter concentration surpasses the minimum threshold typically required for mineral soils, with values between 4.69% and 5.09%. Soil pH ranged from slightly acidic to neutral, depending on the type of solution applied. In inclusion, the soil in the study area demonstrates a good fertility level to support various types of crops. Of course, this research has many impacts or benefits for coffee farmers, for example in the first case, namely, in terms of optimizing or using land management practices, the results of this research can later be used as a basis for agricultural extension materials that will later be used in the field and of course also have an influence on the steps of farmers in handling the land which will certainly have an impact in the future on the productivity of plantation crops, especially in the area. However, further research is recommended to assess climatic and landform factors in order to determine a more comprehensive land suitability classification.